INTEGRATING 'UNITY OF SCIENCE' CONCEPT IN EFL CLASS OF TERTIARY EDUCATION - Siti Tarwiyah (Leksema: Jurnal Bahasa dan Sastra, 2017)
Science, to some extent, is often dichotomized with religion.The concept of unity of science sees science and religion as one unit. This concept confirms that all sciences are from God. As the result, there must be a kind of dialogue between science and religious values. The objective of this study was to describe the characters integrated and the practices to integrate the characters in EFL class through unity of science concept.It was designed qualitatively using questionnaire ocumentation, observation, and Focus Group Discussion for collecting data. The data were accessed from 25 lecturers of English. The integration of unity of science in EFL class were based on the topic of each meeting, e.g. Introduction: Making friends with good people, The importantce of knowing each other and Talking about Past Events : Learning from experience, and it was also done through conditioning students to dress and to behave based on Islamic rules, opening and closing lecture by praying, referring to Qur’anic verses and prophetic tradition, employing moderate and absolute integration. The integration of unity of science concept was found to be essential to produce knowledgable graduates with good characters.